COVID-19 Pandemic and Prevalence of Self-Care Practices among the Future Physicians: A Bangladesh Study - Johora, Fatema; Abbasy, Asma Akter; Jeenia, Fatiha Tasmin; Bhowmik, Mithun Chandro; Aktar, Mohsena; Choudhury, Nargis Akhter; Moitra, Priyanka; Ferdoush, Jannatul (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2021)
Background: Since December 2019, the Novel Coronavirus, SARS-CoV-2, has garnered global attention due to its rapid transmission, which has infected more than twenty nine million people worldwide. World is facing enormous stress and anxiety as there is no effective medicine or vaccine to treat or prevent COVID-19 till date. Experts are recommending self-care like social distancing, respiratory etiquette, hand washing, using face mask to prevent corona virus infection. The aim of the study to describe the pattern of self care practice among the student of Bangladesh during COVID-19. Materials and methods: This descriptive cross-sectional study was designed to assess the prevalence of self-care practice among the undergraduate medical students (4th year) of 14 medical colleges of Bangladesh during COVID-19 pandemic. A structured questionnaire survey linked in the google form was used as study instrument and was distributed among study population through email, messenger, whatsapp and other social media during the month of October 2020. Total 916 students were participated in the study. Results: 79.8% of students reported self-care practice in study period. 44.98% of students went outside once in a week. 90.5%, 70.96% and 52.62% of respondents always used face mask, followed 20 seconds hand washing principle and maintained social distancing. Face masks (97.8%), sanitizers (76.7%) and gloves (71.9%) are most common items purchased as protective mesures. Most of the students (76.9%) follow their hobbies as a coping strategy to overcome phychological stress, while 6% of students took professional help. Conclusion: Suboptimal practice of self-care was found among the undergraduate medical students of Bangladesh. Chatt Maa Shi Hosp Med Coll J; Vol.20 (2); July 2021; Page 22-27